Link analysis an information science approach - Egghe, Leo (Library and information science (New York, N.Y.), 2004)
The web is central to many human activities and infringes on many others: at home, and at work, including education and research. Links between web sites can be used in information science and social science research as a valuable source of evidence about online phenomena, and about online components of offline phenomena. Given a set of websites, the links between them many reveal interesting patterns of connectedness that could reflect issues of underlying human communication or information value. Link analysis is therefore a valuable tool for information science and social science researchers investigating the web, or other phenomena with an offline component. This book provides methods, guidelines and examples to guide researchers and students through a research project, in addition to reviewing a considerable body of previous work. It contains a complete link analysis methodology for information science and social science research. It features a strong online component which includes software and instructions to allow complete link analyses. The case studies include academic, business and commercial search engine applications. Practical chapters describe a range of related methods, software and data sources.